Pelaksanaan Mediasi Menurut PERMA Nomor 1 Tahun 2008 Berikut Permasalahannya - Sholahuddin Harahap (Syiar Hukum, 2011)
In essence, every subject of law both individual and legal entity wants to life peacefully without any dispute with any other member of community. However, the dispute could not be avoided in certain circumstances, so that it has to be settled before a court. It is generally kwown that  a dispute settled through the court conventionally  is very slow and complicated. For this reason, it is necessary for Supreme Court to optimize a peaceful method as set out in Article 130 of HIR or Article 154 of RBG. Such method known as settlement of dispute   through   mediation as regulated by the Supreme Court Regulation No.1 of 2008. Under the Regulation, principal the parties are obliged to  present in mediation. They are given the opportunity to resolve their dispute by mediation out of court to be affirmed. If the expression of a party’s consent to be bound by an agreement has been procured through the coercion, error or fraud of its representative  by another Party, the Party must submit a new claim for the purpose of  agreement cancelation.